Field reports form for submitting seasonal observations of Iowa birds, Ed Thelen, fall 1995 - Thelen, Edet al (1995)
List of birds and locations contributed by Ed Thelen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1995. Epson - sheet feed/flatbed